2017
DOI: 10.1016/j.bbr.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic restraint stress causes a delayed increase in responding for palatable food cues during forced abstinence via a dopamine D1-like receptor-mediated mechanism

Abstract: Relapse to unhealthy eating habits in dieters is often triggered by stress. Animal models, moreover, have confirmed a causal role for acute stress in relapse. The role of chronic stress in relapse vulnerability, however, has received relatively little attention. Therefore, in the present study, we used an abstinence-based relapse model in rats to test the hypothesis that exposure to chronic stress increases subsequent relapse vulnerability. Rats were trained to press a lever for highly palatable food reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
(70 reference statements)
5
11
1
Order By: Relevance
“…Considering the evidence described above, we postulate that stress-coupled food addiction involves different mechanisms. The present study did not detect changes in DR1 levels in the NAc, although a previous study indicated that DR1 is possibly involved in the process of chronic stress. 30 …”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Considering the evidence described above, we postulate that stress-coupled food addiction involves different mechanisms. The present study did not detect changes in DR1 levels in the NAc, although a previous study indicated that DR1 is possibly involved in the process of chronic stress. 30 …”
Section: Discussioncontrasting
confidence: 97%
“…29 When repeatedly exposed to a stressor, mice gradually habituated to the stressor and their food consumption was restored. Mice selectively increase their response to palatable food cues following chronic stress. 30 In addition, chronic stress exposure enhances vulnerability to cue-induced relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine and SCH-23390 were dissolved in 0.9% sterile saline. The dose of SCH-23390 was chosen based on our previous work (Ball et al, 2017; Ball et al, 2015; Ball et al, 2016) and the doses of cocaine were chosen based on pilot data. All doses refer to weight of salt.…”
Section: Methodsmentioning
confidence: 99%
“…On Day 7, a second extinction test was conducted that was identical to the first extinction test, except that it was three hours in length. We chose the 1-week, post-stress time-point for the second extinction test because our previous work showed that chronic restraint stress caused an increase in palatable food seeking 7 days, but not one day, after the last restraint (Ball et al, 2017). See Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation